The critical case of a man called K - Muḥammad, ʻAzīz, 1987- (Hoopoe, 2021)
"K is an introverted man in his mid-twenties, working for a big, faceless petrochemical company. After reading Kafka, K decides to write his own diary, but he is constantly frustrated by his lack of experiences, his concerns about his privacy, and the demands of his dull job and family. When he receives the news that he has leukemia, he finds himself torn between a sense of devastation and a revelation that he has finally found a way out of his writing predicament, as he begins to rebel against the social and economic constrains that threaten to overwhelm him. Through Aziz Mohammed's measured but forceful writing, this is an absorbing, sensitive, and at times darkly humorous telling of K's experience of illness, his contemplation of death, and his determination to maintain his independence of decision through it all"--